Risk factors for intertrochanteric femoral fractures with concomitant lateral wall involvement in elderly women - Shi, Gaolong; Hu, Zhenghui; Xie, Zonggang; Gu, Jun; Lu, Qiyan; Ling, Zhuoyan (Frontiers in Surgery, 2025)
BackgroundIntertrochanteric femoral fractures are common osteoporotic injuries in elderly women, and disruption of the lateral femoral wall has been recognized as a key factor contributing to fracture instability and fixation failure. Low bone mineral density (BMD), impaired bone metabolism, and decreased body mass index (BMI) are known to influence fracture patterns in the elderly; however, the specific factors predisposing patients to concomitant lateral wall involvement remain unclear. Therefore, the purpose of this study was to compare BMD, bone turnover markers, BMI, and age between elderly women with isolated intertrochanteric fractures and those with additional lateral wall involvement, and to identify independent risk factors associated with lateral wall fractures.MethodsBetween January 2023 and February 2024, 49 postmenopausal women with intertrochanteric femoral fractures were treated at our institution. Among them, 29 had isolated intertrochanteric fractures and 20 sustained concomitant lateral wall fractures. Independent-samples t tests were used to compare age, BMI, and BMD between groups, whereas Mann–Whitney U tests were applied for P1NP and β-CTX. Binary logistic regression was performed with age, BMI, lumbar BMD, and hip BMD as covariates to assess their associations with lateral wall involvement.ResultsSignificant differences were observed between groups in age, BMI, lumbar BMD, and hip BMD, whereas P1NP and β-CTX showed no significant differences. Logistic regression revealed that lower BMI, lumbar BMD, and hip BMD were independently associated with the occurrence of lateral wall fractures.ConclusionLow BMI and decreased lumbar and hip BMD are significant risk factors for lateral wall involvement in intertrochanteric femoral fractures among elderly women.Trial RegistrationClinicalTrials.gov identifier: NCT07196982.